Unraveling and Regulating Self-Discharge Behavior of Ti3C2Tx MXene-Based Supercapacitors - Wang, Zixing; Xu, Zhong; Huang, Haichao; Chu, Xiang; Xie, Yanting; Xiong, Da; Yan, Cheng; Zhao, Haibo; Zhang, Haitao; Yang, Weiqing (ACS nano, 2020)
Rich chemistry and surface functionalization provide MXenes enhanced electrochemical activity yet severely exacerbate their self-discharge behavior in supercapacitors. However, this self-discharge behavior and its related mechanism are still remaining issues. Herein, we propose a chemically interface-tailored regulation strategy to successfully unravel and efficiently alleviate the self-discharge behavior of Ti3C2Tx MXene-based supercapacitors. As a result, Ti3C2Tx MXenes with fewer F elements (∼0.65 atom %) show a positive self-discharge rate decline of ∼20% in comparison with MXenes with higher F elements (∼8.09 atom %). Such decline of the F elements can highly increase tight-bonding ions corresponding to an individual self-discharge process, naturally resulting in a dramatic 50% increase of the transition potential (VT). Therefore, the mixed self-discharge rate from both tight-bonding (contain fewer F elements) and loose-bonding ions (contain more F elements) is accordingly lowered. Through chemically interface-tailored engineering, the significantly changed average oxidation state and local coordination information on MXene affected the interaction of ion counterparts, which was evidently revealed by X-ray absorption fine structures. Theoretically, this greatly improved self-discharge performance was proven to be from higher adsorption energy between the interface of the electrode and the electrolyte by density functional theory. Therefore, this chemically interface-tailored regulation strategy can guide the design of high-performance MXene-based supercapacitors with low self-discharge behavior and will promote its wider commercial applications.Rich chemistry and surface functionalization provide MXenes enhanced electrochemical activity yet severely exacerbate their self-discharge behavior in supercapacitors. However, this self-discharge behavior and its related mechanism are still remaining issues. Herein, we propose a chemically interface-tailored regulation strategy to successfully unravel and efficiently alleviate the self-discharge behavior of Ti3C2Tx MXene-based supercapacitors. As a result, Ti3C2Tx MXenes with fewer F elements (∼0.65 atom %) show a positive self-discharge rate decline of ∼20% in comparison with MXenes with higher F elements (∼8.09 atom %). Such decline of the F elements can highly increase tight-bonding ions corresponding to an individual self-discharge process, naturally resulting in a dramatic 50% increase of the transition potential (VT). Therefore, the mixed self-discharge rate from both tight-bonding (contain fewer F elements) and loose-bonding ions (contain more F elements) is accordingly lowered. Through chemically interface-tailored engineering, the significantly changed average oxidation state and local coordination information on MXene affected the interaction of ion counterparts, which was evidently revealed by X-ray absorption fine structures. Theoretically, this greatly improved self-discharge performance was proven to be from higher adsorption energy between the interface of the electrode and the electrolyte by density functional theory. Therefore, this chemically interface-tailored regulation strategy can guide the design of high-performance MXene-based supercapacitors with low self-discharge behavior and will promote its wider commercial applications.